Analisa Model Bisnis Radio Suara Surabaya dan Pengembangannya di Era Disruptive Technology - Teguh Santoso; Jovita Vicka Bayu Wardhani (University of Merdeka Malang, 2018)
The speed of ICT developments, specifically in internet and mobile technologies, have highlighted the rising importance of the Business Model (BM) in the digital economy era. Digital business is very complex, dynamic and high levels of uncertainty and competition (disruptive). This study analyzes how Radio Suara Surabaya adopts and employs the convergence media in their business activities to anticipate and exploit the opportunity within the disruptive era. The data collection technique uses a mixed methods model Sequential Exploratory Design, where qualitative data includes semi-structured interviews, observations, discusion group focus with stakeholders, while quantitative data includes distributing questionnaires to stakeholders. This study reveal that the adoption of convergence media conducted by Radio Suara Surabaya can maintain their existence within the turbulent business landscape. https://doi.org/10.26905/jmdk.v6i2.2435